Towards a marine strategy for the deep Mediterranean Sea: Analysis of current ecological status. (February 2020) - ,; Angeletti, L.; Barsanti, M.; Borg, J.A.; Bosso, M.; Brind'Amour, A.; Castellan, G.; Conte, F.; Delbono, I.; Galgani, F.; Morgana, G.; Prato, S.; et al.
Abstract: The Marine Strategy Framework Directive (MSFD), introduced in June 2008, was adopted to achieve a Good Environmental Status (GES) in the EU's marine waters and to protect resources of socio-economic interest. The MSFD exerts to the marine area over which a Member State exercises jurisdictional rights in accordance with the United Nations Convention on the Law of the Sea (UNCLOS), including the deep-sea waters, seafloor and sub-seafloor of the Exclusive Economic Zones (EEZ). However, currently the MSFD focuses on coastal habitats and the shallow-water seafloor to the detriment of the deeper habitats. Despite the huge dimension of the deep sea (below 200 m of depth) covering more than 65% of the Earth's surface and including >95% of the global biosphere, the relevance of the dark portion of the seas and oceans is still almost completely neglected. Given the important bi-directional links between shallow and deep ecosystems, there is a clear need for extending the implementation of the MSFD into the deep sea, to define a sound ecosystem-based approach for the management and protection of deep-sea ecosystems and attain GES. We assembled data on drivers, anthropogenic pressures and impacts concerning the MSFD descriptors pertaining to the Mediterranean deep sea. We list deep-sea monitoring activities and the main sources providing benchmark conditions, and discuss knowledge and geographic coverage gaps. MSFD descriptors apply to the deep sea as to coastal waters, and ought to be monitored contemporaneously. We provide recommendations for guidelines for future deep-sea monitoring in the Mediterranean Sea. Highlights: MSFD fails to cover the huge dimension of deep-sea environments and important bi-directional link with shallow ones. Extending MSFD to the deep sea and defining an ecosystem-based approach for its management and protection is urgently needed. Data on drivers, anthropogenic pressures and impacts regarding the MSFD descriptors for deep-sea Mediterranean were reviewed. Deep-sea monitoring activities were discussed and knowledge and geographic coverage gaps evidenced. Recommendations for guidelines for future deep-sea monitoring were provided.